Placental galectin-3 is reduced in early-onset preeclampsia - Kandel, Manju; Tong, Stephen; Walker, Susan P; Cannon, Ping; Nguyen, Tuong-Vi; MacDonald, Teresa M.; Hannan, Natalie J.; Kaitu’u-Lino, Tu’uhevaha J.; Bartho, Lucy A (Frontiers in Physiology, 2022)
Preeclampsia is a disease of pregnancy responsible for significant maternal and neonatal mortality. Galectin-3 is a β-galactoside binding protein. This study aimed to characterise galectin-3 in women with preeclampsia and human trophoblast stem cells (hTSCs). Galectin-3 was measured in placental lysates and plasma collected from patients with early-onset preeclampsia (delivered <34 weeks’ gestation) and gestation matched controls. Placental galectin-3 protein was significantly reduced in 43 women with early-onset preeclampsia compared to 21 controls. mRNA expression of LGALS3 (galectin-3 encoding gene) was reduced in 29 women with early-onset preeclampsia, compared to 18 controls (p=0.009). There was no significant difference in plasma galectin-3 protein in 46 women with early-onset preeclampsia compared to 20 controls. In a separate cohort of samples collected at 36 weeks’ gestation, circulating galectin-3 was not altered in 23 women who later developed preeclampsia, versus 182 who did not. In syncytialised hTSCs, hypoxia increased mRNA expression of LGALS3 (p=0.01). Treatment with inflammatory cytokines (TNF-α and IL-6) had no effect on LGALS3 mRNA expression. However, TNF-α treatment caused an increase in mRNA expression of LGALS3BP (galectin-3 binding protein encoding gene) in hTSCs (p=0.03). This study showed a reduction of galectin-3 in placenta from pregnancies complicated by early-onset preeclampsia. LGALS3 mRNA expression was dysregulated by hypoxia exposure in placental stem cells.